Intraoperative Squash Smear in Central Nervous System Lesions and Its Correlation with Histopathology - Patil, Vijayalaxmi S; Hippargi, Surekha B; K, Mamatha; Jawalkar, Sneha; Chulki, Sai (Annals of Pathology and Laboratory Medicine, 2024)
Background: Space-occupying lesions (SOLs) of the central nervous system (CNS) are a significant cause of neurological morbidity and mortality. Intraoperative squash smear cytology is a simple and reliable technique for the rapid intraoperative diagnosis of neurosurgical specimens. It has proven particularly valuable in diagnosing CNS tumors and aids the surgeon in planning the extent of surgery. This study was designed to assess the accuracy of intraoperative squash smear in diagnosing central nervous system (CNS) space-occupying lesions. Methods: This study was a retrospective observational study consisting of 41 patients diagnosed with space-occupying lesions in the CNS. Smears were prepared from the biopsy sample obtained at the time of operation and were stained with rapid hematoxylin and eosin, Papanicolaou stain. The cytological diagnosis offered intraoperatively was compared with the histopathological diagnosis. WHO classification of CNS tumors 2021 was used to classify tumors. Results: Among the forty-one cases studied, thirty-four cases showed complete correlation with histopathology, five cases showed partial correlation, and two cases were discrepant. The diagnostic accuracy was 82.9% by complete concordance and increased to 95% on applying partial concordance criteria. Conclusion: Intraoperative squash smear cytology is a simple, rapid, cost-effective method and provides diagnosis with fair accuracy in brain lesions, especially brain tumors, and is of great value in intraoperative consultation.